Reliability of Typhidot-M in diagnosis of typhoid fever in children - Nithya M; Jamdade, Shrikant; Kannan N; Mitra, Nibedita (Asian Journal of Medical Sciences, 2022)
Background: Typhoid fever continues to be endemic and a major cause of mortality and morbidity in the developing countries. Many times, it presents a diagnostic challenge to treating physicians due to overlapping clinical features with other common causes of acute fever. A rapid and reliable laboratory test would be of great help to clinicians for early diagnosis and appropriate treatment of typhoid fever. Aims and Objectives: The present study was conducted to assess the reliability of Typhidot-M in diagnosis of typhoid fever. Materials and Methods: A total of 203 children with clinical features consistent with typhoid fever were enrolled in the study. Blood culture, Typhidot-M, and Widal test were performed. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated for Typhidot-M and Widal test in comparison with blood culture as reference standard. Results: Out of 203 patients, 30 (14.8%) were blood culture positive. One hundred and six patients were Typhidot-M positive and 97 were negative. Typhidot-M had a sensitivity of 93.3%, specificity of 54.9%, and PPV and NPV of 26.4% and 97.9%, respectively. Conclusion: Typhidot-M is a sensitive test for early diagnosis of typhoid fever. However due to low specificity, positive results should be correlated with clinical picture and other possible diagnoses.